The effects of heat adaptation on physiology, perception and exercise performance in the heat: A meta-analysis - Tyler, C. J.; Reeve, T.; Hodges, G. J.; Cheung, S. C. (Sports Medicine, 2016)
Exercise performance and capacity are impaired in hot, compared to temperate, conditions. Heat adaptation (HA) is one intervention commonly adopted to reduce this impairment because it may induce beneficial exercise performance and physiological and perceptual adaptations. A number of investigations have been conducted on HA but, due to large methodological differences, the effectiveness of different HA regimens remain unclear. Objectives: (1) To quantify the effect of different HA regimens on exercise performance and the physiological and perceptual responses to subsequent heat exposure. (2) To offer practical HA recommendations and suggestions for future HA research based upon a systematic and quantitative synthesis of the literature. Data Source